9x-27=8x-7

Simple and best practice solution for 9x-27=8x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-27=8x-7 equation:


Simplifying
9x + -27 = 8x + -7

Reorder the terms:
-27 + 9x = 8x + -7

Reorder the terms:
-27 + 9x = -7 + 8x

Solving
-27 + 9x = -7 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-27 + 9x + -8x = -7 + 8x + -8x

Combine like terms: 9x + -8x = 1x
-27 + 1x = -7 + 8x + -8x

Combine like terms: 8x + -8x = 0
-27 + 1x = -7 + 0
-27 + 1x = -7

Add '27' to each side of the equation.
-27 + 27 + 1x = -7 + 27

Combine like terms: -27 + 27 = 0
0 + 1x = -7 + 27
1x = -7 + 27

Combine like terms: -7 + 27 = 20
1x = 20

Divide each side by '1'.
x = 20

Simplifying
x = 20

See similar equations:

| 4n^2+4n-35=0 | | 4y+1Y= | | 3x-45=8x | | 2x-30=-x | | -6+m=9 | | 5p^4-2q^4-10=0 | | -7x-2y=11 | | -9+x=14 | | -8x-4=16 | | 3n^2-12n+9=0 | | 8+5x=42 | | j+(-7)=-1 | | 4*2/3-1 | | p-(-7)=-2 | | 3x+99=-2x-1 | | 81m^4+106m^2+25=0 | | (-10)+m=(-2) | | -5x+68=-7x+8-3x | | 5.5=10em-5 | | -17+x=-12 | | r-5=-1 | | 3x+77=-6x-4 | | m-5=12-9+1 | | -3+y=19 | | 0=16t^2+8t+15 | | -12x-17=-13x+7+9x | | -10x^2-27xy-5y^2=0 | | 7x^2-56x-21=0 | | 0.02(60)+0.04x=0.03(50+x) | | -5x^2+6x+6=0 | | k-3=24 | | -x^2+2x-8=0 |

Equations solver categories